The Impact Of Sundaries To Improve Production And Welfare (Case study Cabai Sundari Innovation Desa Lembor District Brondong Lamongan District East Java Province) - Abid Muhtarom; Bambang Eko Muljono; Zulkifli Lubis; Nuril Badriyah; Abdul Ghofur; Husen - (Trunojoyo University of Madura, 2018)
Chili Sundari, Farmers Innovation So Superior Product Lembor Village, Brondong District, Lamongan Regency, East Java Province is a blessing for the people of Lembor village, because of the innovation of this product, the potential of the village can be done and explored more deeply and systematically.The type of research used is quantitative research. Quantitative research is a research by collecting data that is numerical then using statistical procedures to obtain information behind the image. The location of this research is Lembor Village, Brondong District, Lamongan Regency, East Java Province, where the data used in this research are primary and secondary data. Primary data in this research is questionnaire.The increase of new superior product type make a big impact on Chili farm sector so that it can increase the production of chili farming. And theoretically the economy can improve the welfare of farmers with increased income perkapital farmers